Sleep problems and associated factors in a rural population of a Southern Brazilian city - Adriana Kramer Fiala Machado; Andrea Wendt; Fernando César Wehrmeister (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To estimate the average of a sleep problems score and their associated factors in adults living in rural areas. METHODS A population-based cross-sectional study with individuals from the rural area of the city of Pelotas, Southern Brazil. Twenty-four of the 50 census tracts that make up the eight rural districts of the city were randomly selected. Individuals of 18 years of age or older residing in the households chosen were considered eligible. Sleep problems were measured using the Mini Sleep Questionnaire, which ranged from 10 to 70 points and the higher the score, the greater the sleep problems. The independent variables evaluated included socioeconomic, demographic, behavioral and health characteristics. In the analysis, linear regression was used, obeying a previous hierarchical model. RESULTS The sample consisted of 1,421 individuals. The average obtained for sleep problems was 29.4 points (95%CI 28.7-30.1). After adjusted analysis, the following variables were associated factors for greater sleep problems: female sex, age greater than or equal to 40 years, lower schooling level, depressive symptoms, pesticide poisoning, and poorer quality of life. CONCLUSIONS The Mini Sleep Questionnaire average in this study was 4.4 points above the cut-off point that established sleep problems. The total points found in the score was high for the rural population. Strategies to improve sleep for these individuals should be focused on higher-risk groups such as women and the elderly and those with pesticide poisoning.